EFFECTIVENESS OF ANNONA MURICATA (SOURSOP) ON VARIOUS TYPES OF CANCER: A SYSTEMATIC REVIEW - Lydia Halette L, Prabu D, Savitha S, Dinesh Dhamodhar, Sindhu R, Rajmohan M (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Annona muricata has long been used as a cancer treatment herb; it is also known by the names graviola, soursop, and guanabana. A. muricata’s mode of action and effectiveness in the treatment of cancer have been well examined. This systematic review set out to compile the body of research on the variables associated with A. muricata extract’s anticancer properties. Methods: The studies included were in-vitro, preclinical animal, and human studies written in English. Studies assessing A. muricata extract and its anticancer activity on a variety of deadly cancers were searched in PubMed, Elsevier Science Direct, Wiley Online Library, Ovid Medline, Cochrane, Ovid Medline, and Prospero databases between the start of the study and June 2022. The findings suggest that A. muricata and its constituents have anticancer effects. However, the amount and length of time used in research on animals to illustrate toxic effects might not be promptly applicable to human effects. The current review’s overall conclusion suggests that A. muricata has a favourable anticancer profile. Future research into its use in people with a variety of cancers is required.